Gaming the system: how predators induce prey to make themselves more vulnerable - Ydenberg, Ron; Young, Sherry; Sullivan-Lord, Rachel (Frontiers in Ethology, 2023)
We describe a natural situation that supports predictions of theoretical scenarios in which predators tactically influence the food - safety trade-off faced by prey to increase their vulnerability. By using low-cost ‘false attacks’ or otherwise advertising their presence, predators force prey to spend time in refuges or in other forms of safety-enhancing behavior, during which foraging is impaired or impossible. Prey must compensate by taking extra risks at other times or places to meet their energy requirements, and as a consequence become easier to capture. We used data on the occurrence of over-ocean flocking (OOF) by Pacific dunlins (Calidris alpina pacifica), and on the timing and success of attacks by peregrines. OOF is a safe but energetically expensive alternative to traditional roosting, and largely replaced the latter in Boundary Bay of southwest British Columbia as the presence of wintering peregrines rose during the 1990s. Peregrines appear to use ‘false’ or ‘non-serious’ attacks to shift the occurrence of OOF to a tidal time frame earlier than is ideal for dunlins, thereby creating later hunting opportunities during which dunlins were vulnerable than otherwise would have been the case. The shift increased dunlin mortality substantially. Tactics used by predators such as prominent perching, salient signals and unpredictable appearances, could have evolved because this forces prey to increase their level of caution, rendering them more vulnerable at other times or places.